The cultivation of dramatic arts: Based on kierkegaardian existential philosophy (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article analyses the way in which Danish philosopher Søren Kierkegaard’s (1813-1855) reflections on the relationship between communication and existence can function as the conceptual foundation for developing a consideration on the cultivation of dramatic arts. Opposing objective communicative forms to those of subjectivity, Kierkegaard makes use of the concept of primitivity as a means of indicating a way of being in which individuals are faced with the phenomenon of their own existence. This article employs theoretical-practical reflections within theatre pedagogy as proposed by Stanislávksi, Knebel and Ward in order to point to the way in which this Kierkegaardian approach allows one to understand the cultivation of the dramatic arts under an existential-communicative light.
Keywords: Existential philosophy; Theatre pedagogy; Dramatic arts; Primitivity; Søren Kierkegaard